Prevalence of Midface Fractures-A Retrospective Institution Based study - XAVIER, SOYA ALFRED; WAHAB, ABDUL; SIVAKUMAR, M. (The journal of contemporary issues in business and government, 2021)
The aim of this study was to evaluate the prevalence of midface fractures among different age groups. A retrospective study was conducted among patients who reported with a history of midface fracture to the Department of Oral and Maxillofacial Surgery during July 2019 - March 2020 . All the datas were obtained from the case records of the patient. Road traffic accidents are the most common cause for midface fractures. Individuals greater than 30 years were the ones mostly affected by midface fractures . They accounted to about 52% of the total population in the study. Dentoalveolar fracture is the most common fracture of the midface. A total of 23% of cases were reported to have dentoalveolar fractures. Chi Square test was used to find the association between the age and midface fracture. P value of 0.4 was obtained , which was statistically insignificant. From this small sampled single centre retrospective study it was concluded that midface fractures were mostly contributed by road traffic accidents in middle aged males.